2021
DOI: 10.3390/children8010036
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Activity-Based Therapy on Respiratory Outcomes in a Medically Complex Child

Abstract: Introduction: Activity-based therapies (ABTs) focus on activating the neuromuscular system below the level of spinal cord injury (SCI) promoting neuromuscular capacity. Case description: A 2 year 7 month old with history of prematurity at 29 weeks, neonatal epidural abscess, resultant cervical SCI, respiratory failure, and global developmental delays presented for enrollment in an outpatient activity-based therapy program. Upon presentation to this program, he required nighttime mechanical ventilation via trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…This association between postural control, gross motor function, and mobility as scored on the GMFM is consistent with observations in children with cerebral palsy (Butler et al, 2010) and gains in trunk control likely contributed to gains in GMFCS level. Recent studies show that children with SCIs who received 60 ABLT sessions or more showed improved trunk control based on Segmental Assessment of Trunk Control scores (Argetsinger et al, 2019, 2020; Behrman et al, 2019; Goode‐Roberts et al, 2021). Mechanisms for improved trunk control align with those activating the neuromuscular system below the lesion via sensory input during ABLT (Angeli et al, 2014; Rejc & Angeli, 2019), as well as potential activation of trunk musculature above, across, and below the lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This association between postural control, gross motor function, and mobility as scored on the GMFM is consistent with observations in children with cerebral palsy (Butler et al, 2010) and gains in trunk control likely contributed to gains in GMFCS level. Recent studies show that children with SCIs who received 60 ABLT sessions or more showed improved trunk control based on Segmental Assessment of Trunk Control scores (Argetsinger et al, 2019, 2020; Behrman et al, 2019; Goode‐Roberts et al, 2021). Mechanisms for improved trunk control align with those activating the neuromuscular system below the lesion via sensory input during ABLT (Angeli et al, 2014; Rejc & Angeli, 2019), as well as potential activation of trunk musculature above, across, and below the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Broken line arrow indicates onset of sound stimulus. Scale bars = 500 ms. Bi, biceps brachii; MG, medial gastrocnemius; sound, recorded train blast; TA, tibialis anterior.showed improved trunk control based on Segmental Assessment of Trunk Control scores(Argetsinger et al, 2019(Argetsinger et al, , 2020Behrman et al, 2019;Goode-Roberts et al, 2021). Mechanisms for improved trunk control align with those activating the neuromuscular system below the lesion via sensory input during ABLT(Angeli et al, 2014;Rejc & Angeli, 2019), as well as potential activation of trunk musculature above, across, and below the lesion.…”
mentioning
confidence: 99%